A Tough Egg to Crack. Issue Volume 14:Issue S343(2019) (August 2018) - Lim, Jeremy; van-Trung, Dinh-
Abstract: The sculpting of the Egg Nebula continues to defy a coherent explanation. Bipolar outflows from the center of the nebula have created bipolar optical lobes that are illuminated by searchlight beams; multiple bipolar outflows orthogonal to the lobes create the appearance of a dark lane; and quasi-circular arcs are imprinted on an approximately spherically-symmetric wind from the progenitorAGB-star. Here, we use archival data from ALMA to study at high angular resolution dust and molecular gas at the center of the nebula. We find that: (i) dust is concentrated in multiple blobs that outline the base of the northern optical lobe; (ii) dense molecular gas forms the wall of a channel swept up and compressed by the outflows that created the bipolar optical lobes; (iii) the expansion and illumination center of the nebula lies at or close to center of the outflow channel. We present a simple working model for the Egg Nebula, and highlight the difficulties that any model face for explaining all the features seen in this nebula.